2004
DOI: 10.1172/jci19930
|View full text |Cite
|
Sign up to set email alerts
|

Pre–B cell colony–enhancing factor inhibits neutrophil apoptosis in experimental inflammation and clinical sepsis

Abstract: Pre-B cell colony-enhancing factor (PBEF) is a highly conserved 52-kDa protein, originally identified as a growth factor for early stage B cells. We show here that PBEF is also upregulated in neutrophils by IL-1β and functions as a novel inhibitor of apoptosis in response to a variety of inflammatory stimuli. Induction of PBEF occurs 5-10 hours after LPS exposure. Prevention of PBEF translation with an antisense oligonucleotide completely abrogates the inhibitory effects of LPS, IL-1, GM-CSF, IL-8, and TNF-α o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
238
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(246 citation statements)
references
References 65 publications
8
238
0
Order By: Relevance
“…Pbef1 is upregulated in neutrophils and monocytes by interleukin-1β, and it functions as a novel inhibitor of apoptosis in response to a variety of inflammatory stimuli during experimental inflammation and clinical sepsis [90]. Its expression is also induced in mammals by lipopolysaccharide and pro-inflammatory cytokines during the infection of human foetal membranes [91].…”
Section: Discussionmentioning
confidence: 99%
“…Pbef1 is upregulated in neutrophils and monocytes by interleukin-1β, and it functions as a novel inhibitor of apoptosis in response to a variety of inflammatory stimuli during experimental inflammation and clinical sepsis [90]. Its expression is also induced in mammals by lipopolysaccharide and pro-inflammatory cytokines during the infection of human foetal membranes [91].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported increased visfatin levels in type 2 diabetes mellitus with or without any correlation with insulin resistance [9,10,11]. Still other studies have reported the effects of visfatin in other conditions, such as metabolic syndrome [12,13,25,26], cardiovascular disease [12,15,26,27,28] and inflammatory status [11,15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported its relationship with type 2 diabetes mellitus [9,10,11] as well as its positive or nonsignificant relationship with insulin resistance [7,12,13,14,15]. Visfatin has also been suggested to play a role in proinflammatory and immunomodulating processes [16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively known as the pre-B cell colony-enhancing factor, studies suggest that visfatin acts as an insulin-mimetic, capable of binding to the insulin receptor and inducing insulin-like effects [1,2]. Associated with obesity and regulated by cytokines known to promote insulin resistance, these observations indicate that visfatin may have a role in the pathogenesis of type II diabetes [3].…”
Section: Introductionmentioning
confidence: 99%